2007
DOI: 10.1080/03630260701641294
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Thalassemic Patients Referred to the Boo Ali Sina Teaching Hospital, Sari, Iran

Abstract: Beta-thalassemia major (TM) is the most prevalent genetic disease in Mazandaran Province. Currently, about 2,700 TM patients have been registered and are under treatment in the province. This study was undertaken to evaluate the survival of patients attending a dedicated clinic at the Boo Ali Sina Teaching Hospital, Sari, Iran, which was established in 1986. This survival analysis was conducted from July 2004 to September 2006. New deaths were updated in September 2006. A total of 1,010 medical records were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 14 publications
1
20
0
Order By: Relevance
“…Similar to our study, Kosaryan et al reported the rate of diastolic dysfunction was 9%; systolic dysfunction, 5%; and severe cardiomyopathy, 5.7%. 21 In a study investigating thalassemia intermedia patients, heart failure was 5.4%; aortic insufficiency, 15.4%; and, mitral valve insufficiency, 47.2%. 22 Cardiac complications were compared with mean ferritin values.…”
mentioning
confidence: 99%
“…Similar to our study, Kosaryan et al reported the rate of diastolic dysfunction was 9%; systolic dysfunction, 5%; and severe cardiomyopathy, 5.7%. 21 In a study investigating thalassemia intermedia patients, heart failure was 5.4%; aortic insufficiency, 15.4%; and, mitral valve insufficiency, 47.2%. 22 Cardiac complications were compared with mean ferritin values.…”
mentioning
confidence: 99%
“…A total of 18 individual papers describing 15 different studies were published between 2000 and 2017, and are summarized in Table . These studies included 7189 patients; however, some patients likely were counted more than once since the multicenter studies from Borgna‐Pignatti et al, although distinct, drew on the same patient populations in Italy .…”
Section: Resultsmentioning
confidence: 99%
“…Only 1 of the retrospective/longitudinal studies compared survival outcomes in β‐thalassemia patients according to the ICT received; a second study compared monotherapy to combination therapy . The remaining studies investigated survival outcomes according to various baseline and treatment characteristics: 1 investigated factors associated with death in a case‐control study; 4 studied outcomes according to compliance with or duration of ICT; 4 compared survival outcomes according to period of treatment (i.e., before or after availability of different iron chelation treatments); 1 measured survival in patients with thalassemia major and thalassemia intermedia before and after introduction of deferoxamine; and 1 measured rates of death in hepatitis C virus (HCV)‐infected and noninfected patients receiving ICT with deferoxamine …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations